Spatio-temporal estimation of integrated water vapour over the peninsular malaysia - Salihin, Suhaila (2020)
Located at a low latitude region, Peninsular Malaysia experiences extreme rainfall and hot weather over various places. The region has a large amount of water vapour in the atmosphere, and its variation shows a close relationship with the monsoon season, leading to severe flood events in some states during the season. Hence, it is important to classify the homogenous characteristic of atmospheric water vapour over this region. However, observing atmospheric water vapour over climatology time period is difficult to enumerate due to its high variability in time and space. Thus, characterizing the water vapour behaviour in the troposphere based on horizontal profile by using Global Positioning System (GPS) meteorology approach has been widely adopted by researchers. However, in this low-latitude region, only a few studies have been conducted due to the lack of GPS Continuously Operating Reference Stations (CORS) infrastructure co-located with the meteorological sensors in this area. Therefore, the aim of this study is to define the behaviour of water vapour in Peninsular Malaysia by utilizing ground-based GPS networks. Three objectives were established for three different research phases. The first objective is to estimate the Zenith Path Delay (ZPD) and Integrated Water Vapour (IWV) from the network of GPS stations. The estimation process of ZPD was performed in post-processed mission and the results were validated with ZPD product by International GNSS Service (IGS). The Root Mean Square (RMS) errors of the GPS-derived ZPD lie between 6 mm to 19 mm. From ZPD, the value of GPS-derived IWV was further extracted and validated with IWV from selected radiosonde stations. Based on the findings, Peninsular Malaysia has high amount of water vapour with an average of >50 kg/m2 over the year. Three GPS stations close to radiosonde stations were assessed and the RMS errors of the GPS-derived IWV were 9.914 kg/m2, 11.154 kg/m2 and 9.865 kg/m2. The results present a good relationship between GPS and radiosonde IWV with linear correlation coefficients of 0.9116, 0.8245 and 0.8369, respectively. The validation results are then addressed in the second phase of the study to fulfil the second objective, which is to assess the estimated GPS ZPD and IWV. The third objective is to characterize the spatio-temporal variability of water vapour in Peninsular Malaysia during monsoon seasons. Two-dimensional (2D) water vapour mapping was generated from IWV results to achieve this objective. Based on the mapping, it was found that the high amount of water vapour can be seen over the west coast of Peninsular during First Inter Monsoon (FIM) with a mean average ranges from 45.482 kg/m2 to 52.973 kg/m2. During the Second Inter Monsoon (SIM) the value of GPS-derived IWV depicts a higher amount of water vapour with a maximum value recorded at 57.429 kg/m2. Further analysis show that North and Northeast of Peninsular Malaysia experienced more water vapour during South West Monsoon (SWM): the mean average lies between 50.505 kg/m2 to 53.305 kg/m2. During North East Monsoon (NEM), less amount of water vapour was recorded in the Northwest and East of Peninsular Malaysia (a mean average of 43.851 kg/m2 to 54.548 kg/m2). However, heavy rain is common in the season, possibly due to the strong monsoon wind that caused the affected area to receive substantial high amount of rainfall. This study has successfully demonstrated the positive trend between GPS-derived IWV and rainfall data.